Analisis Kebutuhan Keterlibatan Orang Tua dalam Pembelajaran Anak di PAUD Mathlaul Anwar - Elizon Nainggolan; Michael Yudha Pratama; Hayunda Aura Sifa; Seni Rasbina Br Karo Sekali; Amelia Paska Sitorus; Milasari Butar Butar; Angel Marantika Siregar (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
Early Childhood Education (PAUD) is a critical period that significantly shapes children’s cognitive, emotional, social, moral, linguistic, and independence development. During this early stage, children experience rapid growth and therefore require consistent, structured, and continuous stimulation from both school and home environments. This study aims to provide a comprehensive analysis of the need for parental involvement in early childhood learning, with a particular focus on PAUD Mathlaul Anwar. A descriptive qualitative method was used through in-depth interviews, classroom observations, and documentation analysis. The findings reveal that most parents show limited involvement due to long working hours, a lack of understanding about early childhood developmental needs, and the perception that teaching is solely the teacher’s responsibility. These conditions lead to various developmental challenges, such as low independence, difficulty following rules, delayed language development, and limited social skills among children. Teachers attempt to address these issues through several strategies, including strengthening communication with parents, providing simple parenting programs, and adjusting learning activities to focus more on independence-building and social emotional development. These findings reinforce the views of Sujiono (2020) and Fitriani (2019), who emphasize that consistent stimulation from parents is essential to ensure meaningful and optimal learning outcomes during early childhood. Therefore, parental involvement is not an optional aspect of early childhood education, but rather a fundamental need that cannot be separated from the learning process in PAUD. Key Words : Parental involvement, early childhood education, need-based principle, child development, community education. Abstrak Pendidikan Anak Usia Dini (PAUD) merupakan periode awal yang sangat menentukan seluruh aspek perkembangan anak. Pada masa usia dini, anak berada dalam fase pertumbuhan pesat sehingga membutuhkan rangsangan yang berkualitas, konsisten, dan berkelanjutan baik di sekolah maupun di rumah. Penelitian ini bertujuan melakukan analisis komprehensif mengenai kebutuhan keterlibatan orang tua dalam pembelajaran anak PAUD, khususnya di PAUD Mathlaul Anwar. Penelitian menggunakan metode kualitatif deskriptif melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa sebagian besar orang tua memiliki keterlibatan yang minim karena faktor kesibukan, kurangnya pemahaman tentang kebutuhan perkembangan anak usia dini, serta persepsi bahwa mendidik adalah tugas guru. Dampaknya terlihat pada kurangnya kemandirian anak, sulitnya anak mengikuti aturan, keterlambatan bahasa, serta lemahnya keterampilan sosial. Guru berupaya mengatasi hal tersebut melalui berbagai strategi seperti meningkatkan komunikasi, memberikan program parenting sederhana, dan menyesuaikan kegiatan belajar agar lebih fokus pada pembentukan kemandirian dan sosial- emosional anak. Hasil penelitian memperkuat pandangan Sujiono (2020) dan Fitriani (2019) bahwa stimulasi yang konsisten dari keluarga sangat menentukan keberhasilan pendidikan pada masa usia dini. Dengan demikian, keterlibatan orang tua bukan hanya pelengkap, tetapi merupakan kebutuhan mendasar yang tidak dapat dipisahkan dari pendidikan PAUD. Kata Kunci : PAUD, keterlibatan orang tua, asas kebutuhan, perkembangan anak usia dini, pendidikan masyarakat.